Access to Innovative Neurological Drugs in Europe: Alignment of Health Technology Assessments Among Three European Countries - Gozzo, Lucia; Romano, Giovanni Luca; Brancati, Serena; Cicciù, Marco; Fiorillo, Luca; Longo, Laura; Vitale, Daniela Cristina; Drago, Filippo (Frontiers in Pharmacology, 2022)
Even for products centrally approved, each European country is responsible for national market access after EMA approval. This step can result in inequalities in terms of access, due to different opinions about the therapeutic value assessed by Health Technology Assessment (HTA) bodies. This study aims to provide a comparative analysis of HTA recommendations issued by EU countries (France, Germany and Italy) for new neurological drugs following EMA approval. In the reference period we identified 11 innovative medicines authorized in Europe for 5 neurological diseases (cerebral adrenoleukodystrophy, spinal muscular atrophy, metachromatic leukodystrophy, migraine, polyneuropathy in patients with hereditary transthyretin amyloidosis), including 8 drugs for genetic rare diseases. We found no agreement on the therapeutic value (in particular the ‘added value’ compared to the standard of care) of the selected drugs. Despite the differences in terms of assessment, the access has been usually guaranteed even if with various type of limitations. The heterogeneity of the HTA assessment of clinical data among Countries is probably related to the uncertainties about clinical value at the time of EMA approval, the lack of long-term data and of direct comparison with available alternatives. Given the importance of new medicines especially for rare diseases, it is crucial to understand and act on the causes of disagreement among the HTA assessments, in order to ensure rapid and uniform access to innovation for patients who can benefit.